Newer antidiabetic drugs and calorie restriction mimicry - Kalra, Sanjay (Indian J Endocrinol Metab, 2016)
De-acceleration of aging and delayed development of age-related morbidity accompanies the restriction of calories (without malnutrition) in laboratory mice, nematodes, yeast, fish, and dogs. Recent results from long-term longitudinal studies conducted on primates have suggested longevity benefits of a 30% restriction of calories in rhesus monkeys as well. Among calorie restricted rhesus monkeys one of the mechanisms for the improvement in lifespan was the reduction in the development of glucose intolerance and cardiovascular disease. Although there are no comparable human studies, it is likely that metabolic and longevity benefits will accompany a reduction in calories in humans as well. However, considering the difficulties in getting healthy adults to limit food intake science has focused on understanding the biochemical processes that accompany calorie restriction (CR) to formulate drugs that would mimic the effects of CR without the need to actually restrict calories. Drugs in this emerging therapeutic field are called CR mimetics. Some of the currently used anti-diabetic agents may have some CR mimetic like effects. This review focuses on the CR mimetic properties of the currently available anti-diabetic agents.